Ovarian Function and Fertility Preservation in Breast Cancer: Should Gonadotropin-Releasing Hormone Agonist be administered to All Premenopausal Patients Receiving Chemotherapy? - Matteo Lambertini; François Richard; Bastien Nguyen; Giulia Viglietti; Cynthia Villarreal-Garza (SAGE Publishing, 2019)
Chemotherapy-induced premature ovarian insufficiency (POI) is one of the potential drawbacks of chemotherapy use of particular concern for newly diagnosed premenopausal breast cancer patients. Temporary ovarian suppression obtained pharmacologically with the administration of a gonadotropin-releasing hormone agonist (GnRHa) during chemotherapy has been specifically developed as a method to counteract chemotherapy-induced gonadotoxicity with the main goal of diminishing the risk of POI. In recent years, important clinical evidence has become available on the efficacy and safety of this strategy that should now be considered a standard option for ovarian function preservation in premenopausal breast cancer patients, including women who are not interested in conceiving after treatment or that would not be candidates for fertility preservation strategies because of their age. Nevertheless, in women interested in fertility preservation, this is not an alternative to gamete cryopreservation, which remains as the first option to be offered. In this setting, temporary ovarian suppression with GnRHa during chemotherapy should be also proposed following gamete cryopreservation or to women who have no access, refuse, or have contraindications to surgical fertility preservation techniques. In this article, we present an overview about the role of temporary ovarian suppression with GnRHa during chemotherapy in breast cancer patients by addressing the available clinical evidence with the aim of identifying both the best candidates for the use of this strategy and the still existing gray zones requiring further investigation.